A situated metacognitive model of the entrepreneurial mindset - Haynie, J. Michael; Shepherd, Dean; Mosakowski, Elaine; Earley, P. Christopher (Journal of Business Venturing, 2010)
We develop a framework to investigate the foundations of an ‘entrepreneurial mindset’ — described by scholars as the ability to sense, act, and mobilize under uncertain conditions. We focus on metacognitive processes that enable the entrepreneur to think beyond or re-organize existing knowledge structures and heuristics, promoting adaptable cognitions in the face of novel and uncertain decision contexts. We integrate disparate streams of literature from social and cognitive psychology toward a model that specifies entrepreneurial metacognition as situated in the entrepreneurial environment. We posit that foundations of an entrepreneurial mindset are metacognitive in nature, and subsequently detail how, and with what consequence, entrepreneurs formulate and inform “higher-order” cognitive strategies in the pursuit of entrepreneurial ends.